Effect of Serum Vitamin D Level on Oral Health Status of Children - Maknunnahar; Hossain, Md Shakhawat; Alam, SM Rowshan; Anwar, Md Mahfuj Ul; Bhuiyan, Mohammad Sayeem Rahman; Numan, Sharker Md; MS, Mohammad Shoaib Chowdhury (Journal of Rangpur Medical College, 2025)
Abstract not available J Rang Med Col. March 2025; Vol.10, No.1: 45-50